Under the influence: environmental factors as modulators of neuroinflammation through the IL-10/IL-10R axis - Bugbee, Eryn; Wang, Angela A.; Gommerman, Jennifer L. (Frontiers in Immunology, 2023)
The IL-10/IL-10 receptor (IL-10R) axis plays an important role in attenuating neuroinflammation in animal models of Multiple Sclerosis (MS) and increased IL-10 has been associated with a positive response to MS disease modifying therapy. Because environmental factors play an important role in MS susceptibility and disease course, identification of environmental factors that impact the IL-10/IL-10R axis has therapeutic potential. In this review, we provide historical and updated perspectives of how IL-10R signaling impacts neuroinflammation, discuss environmental factors and intestinal microbes with known impacts on the IL-10/IL-10R axis, and provide a hypothetical model for how B cells, via their production of IL-10, may be important in conveying environmental “information” to the inflamed central nervous system.